Seeing ophthalmologic problems in Parkinson disease: Results of a visual impairment questionnaire. (7th April 2020) - Borm, Carlijn D.J.M.; Visser, Femke; Werkmann, Mario; de Graaf, Debbie; Putz, Diana; Seppi, Klaus; Poewe, Werner; Vlaar, Annemarie M.M.; Hoyng, Carel; Bloem, Bastiaan R.; Theelen, Thomas; de Vries, Nienke M.
Abstract : Objective: To determine the prevalence and clinical effect of ophthalmologic symptoms in patients with Parkinson disease (PD), compared with controls, using a standardized questionnaire. Methods: In this observational, cross-sectional, multicenter study, 848 patients with PD and 250 healthy controls completed the Visual Impairment in Parkinson's Disease Questionnaire (VIPD-Q). The VIPD-Q addressed 4 domains according to structures: (1) ocular surface; (2) intraocular; (3) oculomotor; and (4) optic nerve. The questionnaire also assessed the effect of ophthalmologic symptoms on daily activities. Results: One or more ophthalmologic symptoms were reported by 82% (95% confidence interval [CI], 80–85) of patients, compared with 48% (95% CI, 42–54) of controls ( p < 0.001). Patients with PD experienced more ophthalmologic symptoms across all domains than controls ( p < 0.001), as reflected by a higher VIPD-Q total score among patients (median 10 [interquartile range (IQR) 13]) than controls (median 2 [IQR 5]; p < 0.001). Ophthalmologic symptoms interfered with daily activities in 68% (95% CI, 65–71) of patients, compared with 35% (95% CI, 29–41) of controls ( p < 0.001). Conclusion: Patients with PD have a higher prevalence of ophthalmologic symptoms than controls. Moreover, these frequently interfere with daily activities. A screening questionnaire such as the VIPD-Q may help with identifying ophthalmologic symptoms in PD, thereby enabling more timely treatment.